Role of Cnot6l in maternal mRNA turnover - Horvat, Filip; Fulka, Helena; Jankele, Radek; Malik, Radek; Jun, Ma; Solcova, Katerina; Sedlacek, Radislav; Vlahovicek, Kristian; Schultz, Richard M; Svoboda, Petr (Life science alliance, 2018)
Removal of poly(A) tail is an important mechanism controlling eukaryotic mRNA turnover. The major eukaryotic deadenylase complex CCR4-NOT contains two deadenylase components, CCR4 and CAF1, for which mammalian CCR4 is encoded by Cnot6 or Cnot6l paralogs. We show that Cnot6l apparently supplies the majority of CCR4 in the maternal CCR4-NOT in mouse, hamster, and bovine oocytes. Deletion of Cnot6l yielded viable mice, but Cnot6l-/- females exhibited ∼40% smaller litter size. The main onset of the phenotype was post-zygotic: fertilized Cnot6l-/- eggs developed slower and arrested more frequently than Cnot6l+/- eggs, suggesting that maternal CNOT6L is necessary for accurate oocyte-to-embryo transition. Transcriptome analysis revealed major transcriptome changes in Cnot6l-/- ovulated eggs and one-cell zygotes. In contrast, minimal transcriptome changes in preovulatory Cnot6l-/- oocytes were consistent with reported Cnot6l mRNA dormancy. A minimal overlap between transcripts sensitive to decapping inhibition and Cnot6l loss suggests that decapping and CNOT6L-mediated deadenylation selectively target distinct subsets of mRNAs during oocyte-to-embryo transition in mouse.